2006
DOI: 10.1007/s11426-006-0256-1
|View full text |Cite
|
Sign up to set email alerts
|

AFM study on the adsorption and aggregation behavior of dissolved humic substances on mica

Abstract: Humic substances constitute the major organic fractions of soils, sediments and natural waters, and play a dominant role in the binding, mobilization, transport and ultimate fate of organic contaminants in subsurface systems. In this paper, two humic acid samples, Guanting and Tianjin, with different origin and chemical compositions have been investigated with AFM imaging for their adsorption and aggregation behaviors on mica. While the Tianjin humic sample is found to form small spheres with 250 to 330 nm in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…And they proposed the likely mechanism that the non-labile fraction was a consequence of a change of conformation of the HA after the binding of pentachlorobenzene [17]. Ge et al observed a more compact conformation of humic substance assemblies after the sorption of naphthalene using atomic force microscopy [40]. As a result, it is possible that the conformation of DOM was changed after binding with solute, which resulted in resistant desorption.…”
Section: Possible Mechanisms Contributing To Desorption Resistancementioning
confidence: 99%
“…And they proposed the likely mechanism that the non-labile fraction was a consequence of a change of conformation of the HA after the binding of pentachlorobenzene [17]. Ge et al observed a more compact conformation of humic substance assemblies after the sorption of naphthalene using atomic force microscopy [40]. As a result, it is possible that the conformation of DOM was changed after binding with solute, which resulted in resistant desorption.…”
Section: Possible Mechanisms Contributing To Desorption Resistancementioning
confidence: 99%
“…However, the opposite effect occurs for anionic metal species such as (AsO 4 ) 3À or (SeO 3 ) 2À which compete with HS for sorption sites Grafe et al, 2001). The morphology of HS sorbed on mineral surfaces, especially mica, has been studied using atomic force microscopy (AFM) to reveal aggregation of organic matter with and without aqueous metal ions (Namjesnik-Dejanovic and Maurice, 1997;Balnois et al, 1999;Maurice and Namjesnik-Dejanovic, 1999;Plaschke et al, 1999;Liu et al, 2000;Ge et al, 2006;Guo and Ma, 2006;Gibson et al, 2007). Using a tapping-mode AFM technique in 20-100 mg C L À1 of NOM solution, Namjesnik-Dejanovic and Maurice (2000) observed that NOM adsorbed on the mica surface from a 100 mM LiCl solution as aggregates with flattened spherical shapes of lateral diameter 1.9-15 nm and thickness of 0.4-0.9 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Also as shown in the NMR results, large amounts of aliphatic groups exist in Aldrich HA while FA is composed of relatively small oligomeric molecules containing predominantly polar and ionizable groups. It has been reported that larger macromolecules of HA that are held together by weak interactions can form a more compact conformation assembly after the sorption of PAHs and may form aggregated hydrophobic regions that are more effective in binding [13,34,35]. As stated above, we can draw the conclusion that the M W of HS might play an important role in binding of PAHs to dissolved humic and fulvic acids.…”
Section: Relationship Between Hs Properties and Binding Affinity For mentioning
confidence: 53%